Method for preparing porous graphite block by grading natural graphite particles
By mixing natural graphite particles of different particle sizes and puffing with concentrated sulfuric acid and hydrogen peroxide, large-porous graphite blocks with high adsorption performance and good recovery properties are prepared, which solves the problems of insufficient performance and difficulty in retrieval of existing expanded graphite particles when adsorbing low viscosity oil or organic solvents.
Patent Information
- Application Number
- CN202411893402.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
When existing expanded graphite particles adsorb low viscosity oil or organic solvents, the space formed between the particles is unfavorable to the adsorption performance. At the same time, the recycling and reuse of disassembled particles is difficult, which limits their application in oil spill treatment.
By mixing natural graphite particles of different preset particle sizes uniformly in proportion, and puffing with concentrated sulfuric acid and hydrogen peroxide, porous graphite blocks with certain mechanical strength and uniform pores were prepared.
The adsorption capacity and recycling performance of low viscosity oil or organic solvents are improved, and the problems of insufficient performance and difficulty in recycling of expanded graphite particles when adsorbing low viscosity oil or organic solvents are solved.
Smart Images

Figure CN119683618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous graphite adsorption materials and preparation thereof, and in particular to a method for preparing a porous graphite block by grading natural graphite particles. Background Art
[0002] During the development, processing, storage and transportation of oil, crude oil or refined oil may leak into the sea due to various reasons. The oil spill will spread rapidly and form an oil film on the sea surface, blocking the dissolution of oxygen in seawater, causing seawater hypoxia, leading to the death of plankton, fish and shrimp, etc., and bringing disastrous consequences to the marine ecological environment. In addition, the benzene and its derivatives contained in oil are volatile. After inhalation by the human body, symptoms such as slow reaction, coma, headache, and tearing will occur, which is also potentially harmful to health. Expanded graphite is a worm-like particle prepared by intercalation and expansion of natural graphite. It has a porous structure and excellent oleophilic and hydrophobic properties, and is an ideal material for treating oil spills. In addition to the adsorption properties of the worm particles themselves, the space formed by the entanglement of particles also has a high adsorption performance for high-viscosity oils.
[0003] However, for the adsorption of low-viscosity oil or organic solvent, the large space between the worm particles is not conducive to improving the adsorption performance. At the same time, the disintegrated expanded graphite particles are difficult to recover and reuse, which hinders the application of expanded graphite in oil spill disposal. Therefore, it is necessary to develop a simple and effective method to achieve the preparation of porous graphite blocks with certain mechanical strength and uniform pores, so as to improve the adsorption capacity and recycling performance of low-viscosity oil or organic solvent. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a method for preparing a porous graphite block by classifying natural graphite particles. The specific content of the invention is as follows: The present invention provides a method for preparing a porous graphite block by classifying natural graphite particles, the method comprising: The natural graphite particles with different preset particle sizes are uniformly mixed in proportion to form a mixed material; The mixed material is expanded by using concentrated sulfuric acid and hydrogen peroxide, and the obtained material is washed, filtered and dried to obtain a porous graphite block; The natural graphite particles with different preset particle sizes include: natural graphite particles with a particle size of -45 μm, natural graphite particles with a particle size of 45 μm to 75 μm, natural graphite particles with a particle size of 75 μm to 270 μm, and natural graphite particles with a particle size of +270 μm.
[0005] Optionally, the mass ratio of the natural graphite particles with a particle size of -45 μm, the natural graphite particles with a particle size of 45 μm to 75 μm, the natural graphite particles with a particle size of 75 μm to 270 μm, and the natural graphite particles with a particle size of +270 μm is 0.5 to 1:1 to 1.5:2.5 to 3.5:4 to 6.
[0006] Optionally, the puffing treatment of the mixed material with concentrated sulfuric acid and hydrogen peroxide includes: uniformly mixing the concentrated sulfuric acid, hydrogen peroxide and the mixed material, standing at room temperature for 3 to 6 hours, and then washing, filtering and drying.
[0007] Optionally, the weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (10-20) mL: (2-5) mL.
[0008] Optionally, the mixed material is expanded using concentrated sulfuric acid and hydrogen peroxide, including: mixing concentrated sulfuric acid, hydrogen peroxide and the mixed material for 0.5-1.5 h, washing, filtering and drying, and then transferring to a closed container, and obtaining a porous graphite block after high-temperature expansion.
[0009] Optionally, the weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (4-8) mL: (0.1-0.5) mL.
[0010] Optionally, the sealed container is a graphite crucible or a corundum crucible with a cover.
[0011] Optionally, the temperature of the high-temperature puffing is 600-1100°C.
[0012] Optionally, the washing, filtering and drying treatments include: using deionized water to perform surface cleaning, transferring the solid matter collected by filtration to an oven, and drying at 80-120°C.
[0013] Optionally, the natural graphite particles of different preset particle sizes are prepared by a natural graphite crushing and classification process.
[0014] Compared with the prior art, the present invention has the following advantages: The present invention provides a method for preparing a porous graphite block by grading natural graphite particles, the method comprising: uniformly mixing natural graphite particles with different preset particle sizes in proportion to form a mixed material; using concentrated sulfuric acid and hydrogen peroxide to expand the mixed material, and washing, filtering and drying the resultant to obtain a porous graphite block; wherein the natural graphite particles with different preset particle sizes include: natural graphite particles with a particle size of -45 μm, natural graphite particles with a particle size of 45 μm to 75 μm, natural graphite particles with a particle size of 75 μm to 270 μm, and natural graphite particles with a particle size of +270 μm.
[0015] The method for preparing a porous graphite block by classifying natural graphite particles provided by the present invention can realize the preparation of a porous graphite block with certain mechanical strength and uniform pores, so as to improve the adsorption capacity and recycling performance of low-viscosity oil or organic solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A flow chart of a method for preparing a porous graphite block by grading natural graphite particles provided in an embodiment of the present invention is shown; Figure 2 The porous graphite block provided by the embodiment of the present invention is shown; Figure 3 Another porous graphite block provided by an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.
[0019] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0020] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.
[0021] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0022] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0023] The present invention provides a method for preparing a porous graphite block by classifying natural graphite particles. Figure 1 The flowchart of the method for preparing porous graphite blocks by classifying natural graphite particles provided in an embodiment of the present invention is shown as follows: Figure 1 As shown, the method includes: S1. Natural graphite particles with different preset particle sizes are uniformly mixed in proportion to form a mixed material; S2. The mixed material is expanded by using concentrated sulfuric acid and hydrogen peroxide, and the obtained material is washed, filtered and dried to obtain a porous graphite block.
[0024] In specific implementation, the natural graphite particles of different preset particle sizes used in the present invention include: natural graphite particles with a particle size of -45 μm, natural graphite particles with a particle size of 45 μm to 75 μm, natural graphite particles with a particle size of 75 μm to 270 μm, and natural graphite particles with a particle size of +270 μm. Since the particle size range of the natural graphite particles used covers -45 μm to +270 μm, these natural graphite particles of different particle sizes are combined together and expanded into a porous graphite block, which can realize that small-sized expanded graphite fills the gaps between large-sized expanded graphite particles, thereby improving the mechanical strength and pore uniformity of the block, and further modifying the adsorption performance of the porous graphite block to low-viscosity oils and organic solvents.
[0025] In some embodiments, the mass ratio of the natural graphite particles with a particle size of -45 μm, the natural graphite particles with a particle size of 45 μm to 75 μm, the natural graphite particles with a particle size of 75 μm to 270 μm, and the natural graphite particles with a particle size of +270 μm is 0.5 to 1: 1 to 1.5: 2.5 to 3.5: 4 to 6. More preferred mass ratios are 0.5: 1: 2.5: 6, 0.5: 1.5: 3.5: 4.5, and 1: 1.5: 3.5: 4.
[0026] In some embodiments, the present invention adopts two methods to uniformly mix the above-mentioned natural graphite particles of different preset particle sizes in proportion to form a mixed material for expansion treatment, one of which is a one-step room temperature expansion method, specifically using concentrated sulfuric acid and hydrogen peroxide to perform a one-step room temperature expansion treatment on the mixed material, including: after the concentrated sulfuric acid, hydrogen peroxide and the mixed material are evenly mixed, standing at room temperature for 3 to 6 hours, using deionized water to wash the surface of the obtained product, filtering and collecting the solid matter, transferring it to an oven, and drying it at 80 to 120°C to obtain a porous graphite block. The weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (10-20) mL: (2-5) mL; another method is a two-step high-temperature expansion method, specifically, the mixed material is pretreated (mixed and stirred) with concentrated sulfuric acid and hydrogen peroxide for 0.5-1.5 h, intercalated substances (graphite oxides) are formed between the carbon layers of natural graphite particles, the surface of natural graphite particles is cleaned with deionized water, the solid matter collected by filtration is transferred to an oven, and dried at 80-120 ° C; the dried natural graphite particles are further transferred to a closed container and subjected to high-temperature expansion at a temperature of 600-1100 ° C, and the preferred high-temperature expansion temperature is 1000 ° C; high temperature causes the oxide layer to decompose, releases a large amount of gas, and the gas expands and further expands the graphite particles, and finally a porous graphite block is obtained. In the process, the weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (4-8) mL: (0.1-0.5) mL.
[0027] The porous graphite blocks obtained by the above two methods have certain mechanical strength and uniform pores, which meet the adsorption requirements for low-viscosity oils and organic solvents; among them, the one-step room temperature expansion method has the advantages of simple operation steps and no need for high-temperature expansion, but the amount of reagents used (concentrated sulfuric acid, hydrogen peroxide) is larger than that of the two-step high-temperature expansion method.
[0028] In some implementations, the sealed container is a graphite crucible or a corundum crucible with a lid.
[0029] In some implementations, the washing, filtering and drying include: using deionized water to perform surface cleaning, transferring the solid matter collected by filtration to an oven, and drying at 80-120°C.
[0030] In some implementations, the natural graphite particles of different preset particle sizes are prepared by a natural graphite crushing and classification process.
[0031] In order to enable those skilled in the art to more clearly understand the present invention, the method for preparing a porous graphite block by classifying natural graphite particles according to the present invention is now described in detail through the following examples.
[0032] The specific implementation contents of the present invention are as follows: Example 1 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed evenly at a mass ratio of 0.5:1:2.5:6, with a total mass of 1 g. The graphite was transferred to a beaker containing 10 mL of concentrated sulfuric acid and stirred in an ice-water bath. 2 mL of hydrogen peroxide was slowly added and stirred for 0.5 h. The mixture was then allowed to stand at room temperature for 3 h. After washing with water to remove acid, filtering and drying at 100 °C, a porous graphite block was obtained. Figure 2 .
[0033] Example 2 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed evenly in a mass ratio of 1:1.5:3.5:4 to a total mass of 1 g. The graphite was transferred to a beaker containing 10 mL of concentrated sulfuric acid and stirred in an ice water bath. After slowly adding 2 mL of hydrogen peroxide, stirring was continued for 0.5 h, and then allowed to stand at room temperature for 3 h. After washing with water to remove acid, filtering and drying at 100 °C, a porous graphite block was obtained.
[0034] (The process of this embodiment is the same as that of embodiment 1. The difference is that the mass ratio of graphite particles in different particle size ranges is mixed at 1:1.5:3.5:4).
[0035] Example 3 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed evenly in a mass ratio of 0.5:1:2.5:6 to a total mass of 1 g. The graphite was transferred to a beaker containing 20 mL of concentrated sulfuric acid and stirred in an ice water bath. After slowly adding 5 mL of hydrogen peroxide and stirring for 0.5 h, it was allowed to stand at room temperature for 3 h. After washing with water to remove acid, filtering and drying at 100 °C, a porous graphite block was obtained.
[0036] (The process of this embodiment is the same as that of embodiment 1. The difference is that the amount of sulfuric acid and hydrogen peroxide used is 20 mL and 5 mL respectively).
[0037] Example 4 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed evenly at a mass ratio of 0.5:1.5:3.5:4.5, with a total mass of 1 g. The graphite was transferred to a beaker containing 4 mL of concentrated sulfuric acid and stirred in an ice-water bath. After slowly adding 0.1 mL of hydrogen peroxide, stirring was continued for 0.5 h. After washing with water to remove acid, filtering, and drying at 100 °C, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 1000 °C to obtain a porous graphite block, see Figure 3 .
[0038] Example 5 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed uniformly in a mass ratio of 1:1.5:3.5:4, with a total mass of 1 g. The graphite was transferred to a beaker containing 4 mL of concentrated sulfuric acid, stirred in an ice-water bath, and 0.1 mL of hydrogen peroxide was slowly added and stirred for 0.5 h. After washing with water to remove acid, filtering, and drying at 100 ° C, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 1000 ° C to obtain a porous graphite block.
[0039] (This embodiment is the same as the process of embodiment 4. The difference is that the mass ratio of graphite particles in different particle size ranges is mixed at 1:1.5:3.5:4).
[0040] Example 6 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed evenly at a mass ratio of 0.5:1.5:3.5:4.5, with a total mass of 1 g. The graphite was transferred to a beaker containing 8 mL of concentrated sulfuric acid, stirred in an ice-water bath, and 0.5 mL of hydrogen peroxide was slowly added and stirred for 0.5 h. After washing with water to remove acid, filtering, and drying at 100 ° C, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 1000 ° C to obtain a porous graphite block.
[0041] (The process of this embodiment is the same as that of embodiment 4. The difference is that the amount of sulfuric acid and hydrogen peroxide used is 8 mL and 0.5 mL respectively) Example 7 Natural graphite particles with particle sizes ranging from -45 μm, 45 μm to 75 μm, 75 μm to 270 μm and +270 μm were mixed at a mass ratio of 0.5:1.5:3.5:4.5 to a total mass of 1 g. The graphite was transferred to a beaker containing 4 mL of concentrated sulfuric acid and stirred in an ice-water bath. After slowly adding 0.1 mL of hydrogen peroxide, stirring was continued for 0.5 h. After washing with water to remove acid, filtering, and drying at 100 ° C, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 600 ° C to obtain a porous graphite block.
[0042] (The process of this embodiment is the same as that of embodiment 4. The difference is that the temperature of high temperature expansion is 600°C) Comparative Example 1 1 g of natural graphite particles with a particle size range of +270 μm was transferred to a beaker containing 4 mL of concentrated sulfuric acid, stirred in an ice-water bath, and slowly added with 0.1 mL of hydrogen peroxide and stirred for 0.5 h. After washing with water to remove acid, filtering and drying, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 1000 °C to obtain a porous graphite block.
[0043] Comparative Example 2 1 g of natural graphite particles with a particle size range of -45 μm was transferred to a beaker containing 4 mL of concentrated sulfuric acid, stirred in an ice-water bath, and slowly added with 0.1 mL of hydrogen peroxide and stirred for 0.5 h. After washing with water to remove acid, filtering and drying, expandable graphite was obtained. The expandable graphite was placed in a graphite crucible with a lid and expanded in a muffle furnace at 1000 °C to obtain a porous graphite block.
[0044] Experimental example At the same time, the porous graphite blocks prepared in the above Examples 1-7 and Comparative Examples 1-2 were placed in a beaker containing diesel for 10 min, taken out and weighed, and the adsorption capacity of diesel was calculated based on the mass difference before and after oil absorption. The test results are shown in Table 1: Table 1 Diesel adsorption capacity of porous graphite blocks
[0045] It can be seen from the test data in Table 1 that the porous graphite block prepared by the graded natural graphite particles provided in the embodiment of the present invention shows a higher diesel adsorption capacity than the graphite block of the comparative example. This shows that the present invention effectively fills the gaps formed between the large-sized expanded graphite particles with the help of small-sized expanded graphite particles through the particle size matching of the natural graphite particles, thereby improving the uniformity of the pores of the graphite block and further improving the adsorption performance of low-viscosity oil.
[0046] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0047] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0048] The method for preparing porous graphite blocks by graded natural graphite particles provided by the present invention is introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing porous graphite blocks by classifying natural graphite particles, characterized in that: The method comprises: The natural graphite particles with different preset particle sizes are uniformly mixed in proportion to form a mixed material; The mixed material is expanded by using concentrated sulfuric acid and hydrogen peroxide to obtain a porous graphite block; The natural graphite particles with different preset particle sizes include: natural graphite particles with a particle size of -45 μm, natural graphite particles with a particle size of 45 μm to 75 μm, natural graphite particles with a particle size of 75 μm to 270 μm, and natural graphite particles with a particle size of +270 μm.
2. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 1, characterized in that: The mass ratio of the natural graphite particles with a particle size of -45 μm, the natural graphite particles with a particle size of 45 μm to 75 μm, the natural graphite particles with a particle size of 75 μm to 270 μm, and the natural graphite particles with a particle size of +270 μm is 0.5 to 1:1 to 1.5:2.5 to 3.5:4 to 6.
3. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 1, characterized in that: The method of using concentrated sulfuric acid and hydrogen peroxide to expand the mixed material comprises: uniformly mixing the concentrated sulfuric acid, hydrogen peroxide and the mixed material, standing the mixed material for 3 to 6 hours at room temperature, and then washing, filtering and drying the mixed material.
4. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 3, characterized in that: The weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (10-20) mL: (2-5) mL.
5. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 4, characterized in that: The method of using concentrated sulfuric acid and hydrogen peroxide to expand the mixed material comprises: mixing concentrated sulfuric acid, hydrogen peroxide and the mixed material for 0.5 to 1.5 hours, washing, filtering and drying, and then transferring the mixed material to a sealed container, and obtaining a porous graphite block after high-temperature expansion.
6. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 5, characterized in that: The weight volume ratio of the mixed material to concentrated sulfuric acid and hydrogen peroxide is 1 g: (4-8) mL: (0.1-0.5) mL.
7. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 5, characterized in that: The sealed container is a graphite crucible or a corundum crucible with a cover.
8. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 5, characterized in that: The temperature of the high temperature expansion is 600-1100°C.
9. The method for preparing a porous graphite block by classifying natural graphite particles according to claim 3 or 5, characterized in that: The washing, filtering and drying treatment comprises: using deionized water to wash the surface, transferring the solid matter collected by filtering to an oven, and drying at 80-120°C.
10. The method for preparing porous graphite blocks by classifying natural graphite particles according to claim 1, characterized in that: The natural graphite particles with different preset particle sizes are prepared through a natural graphite crushing and classification process.
Citation Information
Patent Citations
Flexible graphite impregnant formula and preparation and application process thereof
CN113912421A
High-thermal-conductivity flexible graphite film and preparation method thereof
CN116553534A
Method of producing graphite granules, and graphite granules
JP2014218403A
Heat radiation material having graphite mixture and method for manufacturing the same
US20180126693A1
Alkaline cell having a cathode incorporating enhanced graphite
US6828064B1